The impact of COVID-19 on the future of orthopaedic training in the UK - Dattani , Rupen; Morgan , Catrin; Li, Lily; Brown , Katharine Bennett-; Wharton, Rupert M H (Acta Orthopaedica, 2020)
The COVID-19 pandemic has had a major impact on global healthcare systems, has drastically affected patient care, and has had widespread effects upon medical education. As plans are being devised to reinstate elective surgical services, it is important to consider the impact that the pandemic has had and will continue to have on surgi- cal training. We describe the effect COVID-19 has had at all levels of training in the UK within trauma and orthopae- dics and evaluate how training might change in the future. We found that the COVID-19 pandemic has significantly impacted trainees within trauma and orthopaedics at all levels of training. It had led to reduced operative exposure, cancellations of examinations and courses, and modifications to speciality recruitment and annual appraisals. This cohort of trainees is witnessing novel methods of delivering ortho- paedic services, which will continue to develop and become part of routine practice even once the pandemic has resolved. It will be important to observe the extent to which the rapid changes currently being introduced will impact the personal health, safety, and career progression of current trainees.